2018
DOI: 10.17219/acem/67561
|View full text |Cite
|
Sign up to set email alerts
|

IL-6, IL-1β, and TNF-α only in combination influence the osteoporotic phenotype in Crohn’s patients via bone formation and bone resorption

Abstract: Our results suggest that IL-6, IL-1β, and TNF-α only in combination induced osteoclaststimulating activity represented by the RANKL/OPG ratio in osteoblasts. Dexamethasone further increased this effect in osteoblasts, while decreasing cytokine expression. The results in osteoclasts support a direct and osteoblast-mediated effect on bone resorption. Our in vitro results differentiate for the first time the effect of cytokines on bone turnover as measured in adult CD patients from the additional dexamethasone ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…Together, these results suggest that low‐grade inflammation promotes or is associated with bone loss in some postmenopausal women. Consistent with these findings, men and women with chronic inflammatory diseases such as rheumatoid arthritis (RA), Crohn's disease, and some viral (ie, human immunodeficiency virus [HIV]) infections develop osteoporosis . Despite these observations, questions as to the nature and the contribution of inflammation to postmenopausal osteoporosis have lingered.…”
Section: Introductionmentioning
confidence: 98%
“…Together, these results suggest that low‐grade inflammation promotes or is associated with bone loss in some postmenopausal women. Consistent with these findings, men and women with chronic inflammatory diseases such as rheumatoid arthritis (RA), Crohn's disease, and some viral (ie, human immunodeficiency virus [HIV]) infections develop osteoporosis . Despite these observations, questions as to the nature and the contribution of inflammation to postmenopausal osteoporosis have lingered.…”
Section: Introductionmentioning
confidence: 98%
“…2a-c). None of the single cytokines affected the SLC14A1 mRNA expression; however, when applied in combination (IL-6 10 pg/mL; TNF-alpha 5 pg/mL; and IL-1 beta 1 pg/mL [11]) the cytokines IL-6, TNF-alpha, and IL-1beta induced a significant reduction of SLC14A1 mRNA expression (▶Fig. 2d).…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, identifying the gene(s) responsible for the "switch" from osteogenesis to adipogenesis is of great research interest, as these genes could represent potential targets for the development of anti-osteoporosis drugs. Furthermore, an interaction of cytokines between bone and fat cells has also been observed [10,11]. High levels of cytokines have been found in bone deprived of estrogens, [12][13][14] and this finding shows a positive association with histological bone resorption parameters and a negative association with bone formation parameters.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The small change in IL-1b expression can lead to more changes in some ''downstream factor'' through a cascade reaction. 15 Increased IL-1b levels may upregulate the expression of bone remodeling factors. 13 Iwasaki et al found that increased IL-1b locally or systemically accelerates the rate of tooth movement, indicating that the IL-1b expression level is positively related to the local bone remodeling activity.…”
Section: Resultsmentioning
confidence: 99%